Influencing factors of ethical judgments among government officials : good governance and strengthening internal control - Rabaatul Azira Hassan; Maheran Zakaria; Muhammad Saiful Anuar Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rampant unethical incidences in public sectors have eroded the public trust in government officials. The accusations include the officials being unethical in their actions and eager in enriching themselves instead of protecting the public interest. Indeed, unethical actions are derived from unethical judgments which are influenced by various factors. Applying Hunt and Vitell’s theory, the objective of this study is to examine the ethical judgments in relation to organizational ethical climate, deontological evaluations of rules compliance, and teleological evaluations of perceived consequences. Data were collected from 141 government officials of Kota Bharu municipal council and analyzed using SmartPLS version 3. As hypothesized, the findings supported that organizational ethical climate, deontological evaluations, and teleological evaluations have a significant impact on ethical judgments. This study provides beneficial insights to the government, policy and lawmakers, municipal councils, and academicians in which rule compliance (deontology) can quantify the right over the wrong consequences (teleology) since having a sound organizational ethical climate is vital in the formation of ethical judgments. Hence, it is hoped that enhancing ethical judgments among the officials would regain the public trust in the municipal council and thus align with the country’s aspiration of becoming a corrupt-free nation in due time.